What Predicts Quality of Learners’ Study Efforts? Implicit Beliefs and Interest Are Related to Mastery Goals but Not to Use of Effective Study Strategies - Yan, Veronica X.; Wang, Lisi (Frontiers in Education, 2021)
What goes into motivating students to take effective action? Ideally, students are not only motivated to invest time into their studying, but that they use their time in effective and productive ways. In the present study, we surveyed college undergraduates (N = 366) about how they engage in one of their college courses. Specifically, we explored how their motivation-related implicit beliefs (ease and difficulty mindsets, intelligence mindset; Dweck, 2000; Fisher & Oyserman, 2017) interact with perceived course interest and course importance to predict their achievement goal orientation for the course and the quality of their study strategies. We used a person-centered latent profiles analysis approach categorize meaningful profiles of implicit beliefs. Those who were likely to highly endorse motivation-increasing implicit beliefs and who found a course interesting were also more likely to hold mastery-approach goals; the relationship however was more complicated for performance-approach and performance-avoidance goals. Implicit beliefs profiles themselves did not directly relate to strategy use, but goal orientation did. In particular, mastery-approach goal orientation was uniquely related to all three of the effective study strategies subscales (e.g. elaborative, standard testing, generative testing). Mastery-avoidance was related to less use of elaborative strategies, and performance-goals were not related to any type strategy use. Perceived course importance was positively related to increased passive and elaborative strategies, but not the standard testing or generative testing strategies. We discuss implications for interventions.